(untitled) (Revista Brasileira Multidisciplinar, 2024)
Fire ecology is the field that seeks to study and understand the dynamics of fire in natural environments. The aim of the research was to develop a study of the art of fire ecology in the ecosystems linked to it and to report on the worrying scenario of fires in the Pantanal in 2024. This is a narrative review, in which the bibliographic search was carried out in databases, using targeted themes. Fire occurs in all Brazilian ecosystems, acting as a transforming agent of the landscape and in the evolution of species, where various factors influence its behavior, but not all biomes are as resistant as the Cerrado. The Pantanal, even though it is used to the presence of fire, is less resilient than the Cerrado, mainly due to the increase in frequency, where in 2024, fires in the Pantanal have already broken new records, causing major impacts on the biome.